PEMETAAN KONDISI KERAWANAN PANGAN DI TINGKAT WILAYAH DI KABUPATEN BOJONEGORO (FOOD INSECURITY CONDITIONS MAPPING IN BOJONEGORO REGENCY) - Supardi, Suprapti; Riptanti, Erlyna Wida; Qonita, Aulia (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2012)
This study aimed to map the condition of food insecurity in Bojonegoro region of Bojonegoro. The research design was exploratory research, which was conducted in Bojonegoro. The data used were secondary data issued by the Food Security Agency in Bojonegoro District . The retrieving method of research location was purposively where Bojonegoro suffered flooding almost every year. The result showed that based on the results of the analysis of FNS (Food and Nutrition Awareness System) in the classifi-cation of food security mapping in Bojonegoro showed that out of 28 districts just as much as 9 districts which were yellow, while 19 districts were shown in green. A total of nine districts that had a yellowfood security map showed that the area was not good conditions for food security which included sub Ngraho, Sekar, Gondang, Ngasem, Kepohbaru, Baureno, Sumberejo, Balen and Malo. From 19 districts that constituted the general overview of Bojonegoro indicated that food security conditions of the area was good.